Improving the Efficiency of Open Cathode PEM Fuel Cell Through Hydrogen Flow Control Using Wavelet-Clipping (Journal of Robotics and Control (JRC), 2024)
Open cathode proton exchange membrane fuel cells (OC-PEMFC) are devices that produce electrical energy through an electrochemical reaction between hydrogen and oxygen gas. Rapid load changes often lead to fluctuations in the flow of hydrogen entering the OC-PEMFC system. Increased load directly correlates with higher hydrogen gas consumption. However, if there is a delay in adjusting the gas flow rate to changes in load, it can trigger fluctuations in the amplitude and frequency of the output voltage. This fluctuation ultimately disrupts the stability of the power supply to the load, and reducing efficiency. Therefore, this paper presents a novel hybrid system that integrates wavelet and clipping techniques to regulate a more stable hydrogen flow, enhancing efficiency and accuracy under constant load conditions. A wavelet control system is used to mitigate noise, coupled with amplitude limitation through clipping techniques. This control system is implemented in OC-PEMFC model that is validated with experimental data. The performance analysis of this hybrid system reveals a 1.95 % increase in efficiency and attains high accuracy, as evidenced by a low ISE value of 0.028 during interference.